Stable precursor fragments of vasoactive peptides in umbilical cord blood of term and preterm infants - Koch, Lutz; Dabek, Martin Thomas; Frommhold, David; Pöschl, Johannes (Hormone research in paediatrics, 2011)
Background: Though various neurohormonal systems are concurrently activated during birth, their biological effectors are not always easy to measure due to their short half-life in vivo, instability in biological samples, or very low concentrations. - Methods: Using a recently discovered chemiluminescence assay, we measured the stable precursor fragments mid-regional pro-atrial natriuretic peptide (MR-proANP), mid-regional pro-adrenomedullin (MR-proADM), C-terminal pro-endothelin-1 (CT-proET-1) and C-terminal pro-vasopressin (CT-proAVP or copeptin) immediately after birth in umbilical venous cord blood from 119 infants with a gestational age of 23-42 weeks and evaluated their possible functions. - Results: Cord blood levels of MR-proANP, MR- proADM, CT-proET-1, and CT-proAVP were considerably higher compared with normal adult levels. The CT-proAVP concentrations were 10-fold higher in term, and 70-fold higher in extremely preterm infants. MR-proANP showed 4-fold higher levels in term infants and 20-fold higher levels in extremely preterm infants. Levels of MR-proADM and CT-proET-1 were 2- to 3-fold higher in preterm and term infants. All four parameters showed significantly decreased values with increasing gestational age and a significant correlation between CT-proET-1 and MR-proADM. - Conclusion: Our results indicate that vasoactive and natriuretic mediators play a functionally relevant role in circulatory transition from fetal to neonatal life.